Clopidogrel reduces migraine with aura after transcatheter closure of persistent foramen ovale and atrial septal defects. Issue 9 (15th August 2005) - Wilmshurst, P T; Nightingale, S; Walsh, K P; Morrison, W L
Abstract : Objective: To report the clinical events leading to alteration of an anticoagulation regimen for patients undergoing transcatheter closure of an atrial shunt and how this affected migraine symptoms after the closure procedure. Method: Audit of a change of anticoagulant regimen. Results: In the first few weeks after a closure procedure migraine frequency and severity increased despite treatment with aspirin for six months in 71 patients. Severe attacks of migraine with aura, including status migrainosus, in the first few weeks after transcatheter closure were terminated by addition of clopidogrel to aspirin treatment. Therefore, the anticoagulant regimen was changed with addition of clopidogrel for the first month after the closure procedure (90 procedures in 89 patients). Fewer patients had migraine with aura in the first month after transcatheter closure when taking the combination of clopidogrel and aspirin compared with aspirin alone (11 of 90 (12.2%) v 30 of 71 (42.3%), p < 0.001). Episodes of migraine with aura were more severe and more frequent in patients taking aspirin alone. Conclusion: The combination of clopidogrel for four weeks and aspirin for six months is superior to aspirin alone for six months for preventing migraine with aura after transcatheter closure of an atrial shunt. This beneficial effect of a powerful inhibitor of platelet aggregation suggests that platelets may have a role in pathogenesis of migraine. This may be because of an effect on serotonin stores. Whether clopidogrel has a role in treatment of migraine in other clinical situations requires investigation.